Socio Economic Status of Farmers and their Awareness on Irrigation under Sri Ram Sagar Project Command Area, Andra Pradesh, India - Kumar, K. Avil; Kalpana, D.; Reddy, M. Devender (International Journal of Bio-resource and Stress Management, 2023)
Improvement in irrigation efficiency of projects is vital for the development of country’s economy. For improving irrigation water use efficiency a clear understanding of socio- economic condition and constraints from the point of famers is paramount importance as it regulates the decision making and option behavior of farmers and in order to assess the status on these aspects, a study was taken up under Sri Ram Sagar Project command (2R minor of D51) during 2008-09. The results indicated that 68% farmers were above 40 years of age having good farming experience and 71% were educated. The average per capita land holding size of farmers was 2.05 ha. Farmers were not aware of different water saving technologies as they were not trained on agricultural water management aspects. Non-availability of water in time and prior information about the release of canal water were the major problems perceived by majority of the farmers. Costs associated with accessing, availability water and distance of the land from water source influenced labour input for distributing water. There was tendency to over irrigate the crops in each term of irrigation because of either availability of water is plenty or as a measure of risk avoidance in the wake of uncertainty and unavailability of water in next turn. Majority of the farmers were of the opinion that poor operation and maintance of the irrigation system was the major reason for low water use efficiency and tail end farmers expressed that head reach farmers were using more water than required and it was suggested that bringing awareness on water use and management under canal commands through trainings and exposure visits was important in addition to extensive interaction between irrigation, agricultural and extension activities with the framers to improve on farm water use efficiency, there by project irrigation efficiency.